Histogenesis of the omasum of the buffalo - PANCHAMUKHI, B G; DESAI, M C; PATEL, K B (The Indian Journal of Animal Sciences, 2013)
Histogenesis of the omasum of buffalo from primordial stage to birth was observed. The epithelium of omasum was of early embryonic type and uniformly distributed at CR 2.5 cm. and superficial and basal zone type at CR 3.2 cm. Laminae orders 1 to 5 laminae Were seen at CR 3.2, 4.1, 7.0,9.0 and 50.5 cmrespectively. The core of all the laminae consisted of lamina propria, muscularis mucosae, submucosa and inner musculor layer. The type of epithelium at CR 74.0 cm was stratified squamous With keratinization, similar 10 that of adult, Secondary branches of laminae were seen aL CR 10.2 em and conal papillae al CR 25.5 cm.